2015
DOI: 10.1021/acs.accounts.5b00293
|View full text |Cite
|
Sign up to set email alerts
|

Copper Nanoparticles in Click Chemistry

Abstract: 2The challenges of the 21 st century demand scientific and technological achievements which must be developed under sustainable and environmentally benign practices. In this vein, Click Chemistry and Green Chemistry walk hand in hand on a pathway of rigorous principles which help to safeguard the health of our planet against negligent and uncontrolled production. The copper-catalyzed azide-alkyne cycloaddition (CuAAC), the paradigm of a click reaction, is one of the most reliable and widespread synthetic trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
169
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 252 publications
(177 citation statements)
references
References 76 publications
5
169
0
3
Order By: Relevance
“…The other interesting ways to generate catalytic active species Cu(I) by using Cu (0) NPs is through comproportionation of Cu(0) and Cu(II) in the native oxide layer on the Cu surface [78]. In Alonso's proposed mechanism for the CuNP-catalyzed AAC, Cu(I) acetylides appeared as the true intermediate species [79]. The in-situ generation of CuCl was postulated after acetylene deprotonation, with the concomitant formation of triethylammonium chloride (in the presence of LiCl derived from CuNPs preparation), and the action of the latter on the CuNPs.…”
Section: Introductionmentioning
confidence: 99%
“…The other interesting ways to generate catalytic active species Cu(I) by using Cu (0) NPs is through comproportionation of Cu(0) and Cu(II) in the native oxide layer on the Cu surface [78]. In Alonso's proposed mechanism for the CuNP-catalyzed AAC, Cu(I) acetylides appeared as the true intermediate species [79]. The in-situ generation of CuCl was postulated after acetylene deprotonation, with the concomitant formation of triethylammonium chloride (in the presence of LiCl derived from CuNPs preparation), and the action of the latter on the CuNPs.…”
Section: Introductionmentioning
confidence: 99%
“…35 This provides an alkyne terminated spiropyran for click reactions, providing access to spiropyran conjugation to any azide-bearing molecule/nanoparticle/surface from the benzyl alcohol. 36 These probes demonstrated that functionalization of the indoline ring of spiropyrans has little effect on thiol response but can impart probe selectivity. While spiropyran 5 demonstrated some thiol selectivity, these probes will most likely be glutathione reporters based on the overwhelming levels of GSH intracellulary (1–10 mM).…”
Section: Discussionmentioning
confidence: 99%
“…Click chemistry has been widely used as a novel green chemistry in recent years [32][33][34][35][36][37][38][39][40]. click chemistry provides an extensively approach to quickly synthesized new polymer brushes in highly yields without special purification and serious reaction condition.…”
Section: Introductionmentioning
confidence: 99%